Nickel‐Molybdenum and Nickel‐Tungsten Dithiolates: Hybrid Models for Hydrogenases and Hydrodesulfurization. Issue 28 (1st September 2015) - Schilter, David; Fuller, Amy L.; Gray, Danielle L.
Abstract: The heterobimetallic complexes [(dppe)Ni(pdt)Mo(CO)4 ], [(dcpe)Ni(pdt)Mo(CO)4 ], [(dppe)Ni(pdt)W(CO)4 ] and [(dcpe)Ni(pdt)W(CO)4 ] dppe = Ph2 P(CH2 )2 PPh2 ; dcpe = Cy2 P(CH2 )2 PCy2 ; pdt 2– = – S(CH2 )3 S – have been prepared and structurally characterized. The internuclear separation in these Ni II M 0 species is highly sensitive to diphosphine basicity and is smallest in the dppe complexes wherein the planar Ni centres are electron‐poor and require interaction with the group 6 metal. The Ni II W 0 species [(dppe)Ni(pdt)W(CO)4 ] was converted into its stable conjugate acid [(dppe)Ni(pdt)HW(CO)4 ] +, a rare example of a nickel–tungsten hydride. This Ni II HW II complex is an electrocatalyst for H + reduction and is relevant to both biological and synthetic H2 ‐processing catalysts. Abstract : A family of [(diphosphine)Ni II (1, 3‐propanedithiolato)M 0 (CO)4 ] (M = Mo, W) complexes is described. Structural studies provide insight into the electronic demands of Ni II in these species. Such complexes blend themes from hydrodesulfurization catalysts as well as the nickel–iron hydrogenase enzymes, allowing access to heptacoordinate motifs in a bimetallic scaffold catalytically active for proton reduction.